2006
DOI: 10.1038/sj.bdj.4813253
|View full text |Cite
|
Sign up to set email alerts
|

The prevention of 'dry socket' with topical metronidazole in general dental practice

Abstract: Objective The purpose of the study was to determine if the intra-alveolar application of topical metronidazole gel could reduce the incidence of alveolar osteitis (dry socket) following routine tooth extraction in molar and premolar extraction sites. Design This was a multicentre, double blind, randomised, placebocontrolled clinical trial. A total of 302 patients took part, of which 23 returned with alveolar osteitis. Of these, eight had received the metronidazole gel and 15 the placebo. Setting The study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 19 publications
0
30
0
Order By: Relevance
“…SEKHAR et al 29 and BERGDAHL & HEDSTRÖ M. 7 in their prospective studies compared the systemic perioperative use of metronidazole with placebo and found the incidence of alveolar osteitis and early postoperative infection to be the same in both groups. REEKIE et al 27 in their double-blind study, found no significant difference between the metronidazole and placebo groups. In the present study, only one patient (single socket) developed alveolar osteitis (0.3%) after mandibular third molar removal.…”
Section: Discussionmentioning
confidence: 96%
“…SEKHAR et al 29 and BERGDAHL & HEDSTRÖ M. 7 in their prospective studies compared the systemic perioperative use of metronidazole with placebo and found the incidence of alveolar osteitis and early postoperative infection to be the same in both groups. REEKIE et al 27 in their double-blind study, found no significant difference between the metronidazole and placebo groups. In the present study, only one patient (single socket) developed alveolar osteitis (0.3%) after mandibular third molar removal.…”
Section: Discussionmentioning
confidence: 96%
“…32,33 While it has been demonstrated that metronidazole may reduce the incidence of dry socket, 34 the findings of several research papers do not show any reduction. 25,[35][36][37] The referrals in this audit relate mostly to the main disease processes that dentists treat on a regular basis, namely den tal caries, gingival and periodontal disease, pulpal and peri apical disease. To date surgical dental specialists working in the primary healthcare setting, particularly those relying on NHS funding have restricted most of their clinical activity to these three disease processes, and may have only cared for patients on a short term basis.…”
Section: Researchmentioning
confidence: 99%
“…The management of dry socket is varied34567891112131415, and strategies have varying rate of success19101112131415. Kaya et al11 showed use of alvogyl, Salicept patch, low laser therapy, and curettage with irrigation in dry sockets of 104 patients divided into four groups.…”
Section: Discussionmentioning
confidence: 99%
“…Management of dry socket was initially with anti-bacterial agents458, lavage, anti-fibrinolytic agents, steroidal anti-inflammatory agents, obtundents, and clot supportive agents139101112. The concept of dry socket management is changing toward alternative interventions including plasma rich growth factors, low level laser therapy1112, and other treatments such as the use of honey.…”
Section: Introductionmentioning
confidence: 99%